Professional burnout syndrome among physicians of intensive care units - V. E. Ironosov; K. V. Pshenisnov; Yu. S. Aleksandrovich (Вестник анестезиологии и реаниматологии)
Introduction. Professional burnout syndrome (PBS) in specialists in emergency medicine is one of the global problems of modern health systems, since its presence has a significant impact both on the health of individual employees and the quality of care in general.The objective was to analyze risk factors, peculiarities of the course of professional burnout syndrome and its prevention among physicians of intensive care units based on the data of world literature in order to eliminate them in domestic clinical practice.Materials and methods. The analysis includes 122 publications from abstract databases PubMed and e-library for the period from 2017 to 2023. The search was carried out using keywords: provider burnout syndrome, stress, personality, anesthesiologist, intensive care physician, intensive care unit. After the initial study of abstracts, 72 articles were excluded from the review, where there was no access to the full text or they were devoted to organizational preventive measures.Results. The frequency of professional burnout syndrome among specialists of intensive care units was about 40%, which was significantly higher compared to other medical specialists. It was revealed that PBS is a crisis period in middle-aged specialists due to functional changes in higher nervous activity. The main risk group with the highest probability of developing PBS is the intensive care unit nursing staff. A significant workload combined with a low level of motivation, dissatisfaction with professional activities and the lack of recognition of personal achievements by colleagues and management are key risk factors for the development of emotional burnout syndrome.Conclusion. A high level of professionalism in combination with the spiritual and moral component of the personal life of a specialist and the elimination of reversible negative factors of the medicine of critical conditions will allow with a high probability to prevent the development of professional burnout syndrome.